Realizing Equality by Increasing Disability Participation Through Inclusive Elections in Indonesia - Nurazhar, Syakhila; Agatha, Carissa; Rahmawati, Aulia (KnE Social Sciences, 2025)
The implementation of general elections for Indonesians is a representation of democracy that is held every five years, where candidates for national leaders and civil society participate in the use of their rights to be elected and vote as mandated by Indonesian Law Undang-Undang No. 39 Tahun 1999. For this reason, this research aims to analyze the level of inclusion of peoples with disabilities in the 2024 general election. It uses a descriptive-qualitative approach and secondary data sources that describe the situation faced by disability groups in general elections. This research uses access, participation, control and benefits (APKM) analysis theory to measure the inclusion of people with disabilities in elections. The results showed that the concept of inclusive elections needs to be improved, with the urgency of the 2024 Regional Head Elections, which will be held in the near future, and as a form of effort to grant political rights to peoples with disabilities in accordance with applicable laws and regulations